Maternal health care services utilisation in the context of ‘Abiye’ (safe motherhood) programme in Ondo State, Nigeria - Anthony Idowu Ajayi; Wilson Akpan (BMC Public Health, 2020)
Abstract Background The Nigeria Demographic and Health Survey (NDHS) of 2008 show that Ondo State had the worst maternal outcomes in the South Western region of Nigeria. To address this problem, the “Abiye” (safe motherhood) programme—which included community engagement, health system strengthening and user fee removal— was implemented by the state government. We assessed the use of maternal health care services and its determinants at 5 years after the implementation of this programme using a population-based survey. We also compared the results of our survey to the NDHS 2013 to assess improvement in maternal health care services utilisation. Methods We conducted a population-based survey in 2016 among representative sample of 409 women who had given birth between 2011 and 2015, which were selected using cluster random sampling. We compared the findings of this 2016 survey to the 2013 NDHS, which contains maternal health care services utilisation information of a total of 434 women who gave birth between 2009 and 2013 to assess progress in the use of maternal health care services. We used descriptive and inferential statistics for our data analysis. Results In the 2013 NDHS survey, about 80% of women received antenatal care compared to 98% in the 2016 survey. Our survey shows that the majority of births (85.6%) took place in health facilities compared to only 56.5% in NDHS 2013 survey, which represents a 29.1 percentage points increase. In both surveys, women with primary level of education or less had lower odds of delivering their babies in health facilities. However, while the 2013 NDHS survey shows that women who resided in urban areas were twice more likely to deliver their babies in health facilities compared to those living in rural areas, the 2016 survey shows that urban residence was no longer significantly associated with a higher odds of facility-based child delivery. Conclusion Maternal health services utilisation has improved considerably following the implementation of the “Abiye” initiative. The findings of this study suggest that with community engagement, health system strengthening and user fee removal for the most vulnerable, universal access to and utilisation of maternal health services is possible.